Can There Be Post-Persons and What Can We Learn From Considering Their Possibility? - Neiders, Ivars (ETHICS IN PROGRESS, 2015)
Many prominent bioethicists have recently raised the question of the possibility of moral status enhancement. In this paper I discuss the arguments advanced by Nicholas Agar for the possible existence of the postpersons. I argue that in spite of the many limitations and shortcomings of Agar’s account, there are no conclusive reasons to rule out the possibility of moral status enhancement. However, if post-persons are as they are described by Agar, the fact of their possibility is less interesting and ethically relevant than it might seem. Most importantly, the account of post-persons given by Agar is rather an outcome of some implausible assumptions. I propose that Agar conflates the ethical with the scientific and dismisses the importance of phenomenology in framing our ethical outlook. Also, he seems to follow the assumption made by many utilitarian ethicists that such features as sentience and cognitive capacities have some universal relevance. This accounts for the delusion that we can view our moral attitudes from the point of view of the Universe.